The Role of City Forest: Study of Malang Urban Forest Contribution in Sequestrating Carbondioxide Emition - Latifa, Roimil; Fatmawati, Diani; Fauzi, Ahmad (Metamorfosa: Journal of Biological Sciences, 2021)
Malabar, as an urban forest has a potential in CO 2 sequestration which was not documented yet. This quantitative descriptive research aimed to describe the contribution of Malabar urban forest in CO 2 emission mitigation through calculating the amount of CO 2 absorbed by the forest. The data collection used was non-destructive in which the indicators measured were DBH and the height of the trees with DBH more than 20 cm. The data gained then was analyzed using Alometric Chave formula to obtain the amount of plant biomass, carbon values, and CO 2 values. The results showed that the potential of Malabar rban forest is not optimized yet as the low amount of carbon stored in this forest. Thus, it is suggested to enrich the trees planted with those which can sequestrate CO 2 in much higher amount compare to the exist one.   Kata kunci: CO 2 sequestration, urban forest, Malabar urban forest